The effect of cloud computing on accounting information system effectiveness - Bolzer, Yann (Review of Management, Accounting, and Business Studies, 2025)
The purpose of this research is to determine whether cloud computing technology has an impact on the effectiveness of accounting information systems. This research was conducted in Denpasar, the capital city of Bali Province, and the center of economic and financial activities in Bali Province. The population of the study consists of business entities implementing cloud computing technology in Denpasar, totaling 32,476 according to the data from the Department of Cooperatives, Micro, Small, and Medium Enterprises of Denpasar in 2022. A sample of 100 respondents was selected using the simple random sampling method. The data collected for the study was quantitative and obtained through a Likert scale questionnaire. Validity and reliability tests were performed to ensure the legitimacy and consistency of the measurement instrument. Data analysis involved classic assumption tests such as normality, multicollinearity, and heteroskedasticity. Simple linear regression analysis was conducted to measure the relationship between the independent variable (Cloud Computing Technology) and the dependent variable (Effectiveness of Accounting Information Systems. The research findings demonstrate that cloud computing technology has a statistically significant and positive effect on the effectiveness of accounting information systems. This is supported by a regression coefficient of 0.638 (p = 0.001) and an R² value of 0.228, indicating that 22.8% of the variation in system effectiveness can be explained by the use of cloud computing.